2018
DOI: 10.3389/fmicb.2018.00574
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Intervention Alters Rumen Microbial Community Development in Hu Lambs During Early Life

Abstract: The pre-weaning period is crucial for rumen developmental plasticity, which can have a long-term impact on animal performance. Understanding the rumen microbiota during early life is important to elucidate its potential role in rumen development. In this study, the rumen microbiota of 10-day-old Hu lambs fed either milk replacer (B-10), milk replacer and starter (STA) or milk replacer and starter supplemented with alfalfa (S-ALF) in the pre- (d17, 24, and 38) and post-weaning periods (d45 and 66) were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 65 publications
10
53
2
Order By: Relevance
“…For example, the low abundances of OTU87, OTU83, OTU93 and OTU539 were identified as the important predictor for regimes, which indicated that low abundance bacteria may also paly critical roles in function drifts. Therefore, previous literature (3, 10) only focused on the genera with significantly different abundances may not provide the best conclusion. RandomForest regression is useful and robust method for correlation applications because of its ability of automatically producing accuracy estimation and measuring the variable importance.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the low abundances of OTU87, OTU83, OTU93 and OTU539 were identified as the important predictor for regimes, which indicated that low abundance bacteria may also paly critical roles in function drifts. Therefore, previous literature (3, 10) only focused on the genera with significantly different abundances may not provide the best conclusion. RandomForest regression is useful and robust method for correlation applications because of its ability of automatically producing accuracy estimation and measuring the variable importance.…”
Section: Discussionmentioning
confidence: 97%
“…An extra alfalfa supplementation on the basis of concentrate diets improves rumen development to the next level. Previous studies reported that increases of growth performance and changes of ruminal microbiota during the pre- and post-weaning periods were found in lambs fed starter plus alfalfa compared with lambs fed fluid-diet and starter (9, 10). In addition, some studies have summarized the significant changes of microbiota in solid feeding regime and evenly calculated the correlation between macronutrient intake and rumen bacterial abundances.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, 20% ramie proportion significantly increased the relative abundance of Treponema . It was reported that Treponema was closely associated with pectin‐rich diet due to the pectin‐degradation ability of species in this genus (Liu, Pu, Xie, Wang, & Liu, ; Yang et al, ). As mentioned earlier, ramie is rich in pectin (Bhattacharya & Shah, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that FMT could regulate tryptophan metabolism by the newborn piglets intestinal micro ora, potentially contributing intestinal barrier maintenance [15]. Yang et al demonstrated that early supplementation with Alfalfa stimulated changes to the ruminal micro ora both before and after weaning [16]. Using highthroughput sequencing of the 16S rRNA gene, Wang et al reported that the colostrum microbiota is signi cantly different from the microbial population observed in the feces of both calf and cattle.…”
Section: Introductionmentioning
confidence: 99%